Assessment of BMI and venous thromboembolism rates in patients on standard chemoprophylaxis regimens after undergoing free tissue transfer to the head and neck - Saadoun, Rakan; Bengur, Fuat Baris; Moroni, Elizabeth A.; Surucu, Yusuf; Veit, Johannes Adrian; Khan, Nayel I.; Daniels, Kelly; Rothenberger, Scott D.; Kubik, Mark; Solari, Mario G.; Sridharan, Shaum (JAMA otolaryngology - head & neck surgery, 2022)
This cohort study assesses whether there is an association between body mass index and postoperative venous thromboembolism and hematoma rates in patients treated with prophylactic enoxaparin 30 mg twice daily.
Gesehen am 23.07.2024